Russia`s Cultural Diplomacy in the Current Geopolitical Context - Alina STOICA; Ana ORJUHOVSCHI (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
In the context of geopolitical tensions at the eastern border of the European Union, cultural diplomacy is becoming a symbolic battleground for regional influence, with significant implications for security and stability in the region. The use of this soft power, which complements traditional foreign policy strategies, is aimed at strengthening relations with partner countries, countering negative narratives or attracting/maintaining sympathy with states where the state in question has political, economic, etc. interests. The context of the current world order, also generated by recent RussianUkrainian relations, is giving rise to numerous debates within international society and academia. Among these, an important aspect is cultural diplomacy's role in the current military conflict context on the EU's eastern border. We are considering the unique way, distinct from the approaches of Western states, of promoting Russia's national interests through cultural diplomacy. The Kremlin has built a complex apparatus for realizing and disseminating information intended to be brought to the attention of public opinion and authorities in the international arena. These actions integrate actors from different levels and carry out complex influencing activities.